2009
DOI: 10.1089/apc.2008.0118
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ultrasound for Use in Detecting Lipoatrophy in HIV-Infected Patients Taking Combination Antiretroviral Therapy

Abstract: The aim of this study was evaluation of ultrasound (US) as a tool for the assessment of lipoatrophy in a population of HIV-infected patients. We enrolled a convenience sample of 151 HIV-infected Caucasian participants (males, 79%) who were treated for at least 1 year with combination antiretroviral therapy (CART) in Zagreb, Croatia. US measurements of subcutaneous fat thickness were done over the malar, brachial, and crural region. We determined sensitivity and specificity of US as a diagnostic tool for lipoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These techniques, however, are not used in everyday clinical practice due to cost and lack of availability. Ultrasound imaging is an emerging alternate quantitative tool that is accurate as well as comparatively affordable and accessible 5 .…”
Section: Introductionmentioning
confidence: 99%
“…These techniques, however, are not used in everyday clinical practice due to cost and lack of availability. Ultrasound imaging is an emerging alternate quantitative tool that is accurate as well as comparatively affordable and accessible 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though, they still regard the ultrasound as a potential tool for the evaluation of the patients, keeping in mind its low cost, accessibility and absence of radiation. 29 In view of all these limitations, the reports of loss or accumulation of fat in specific areas and the determination of the intensity level clinically evaluated and concordant between doctor and patient remain the best way of defining the problem individually. 27 Most studies about lipodystrophic syndrome are based on the presence of subjective symptoms reported by patients, on the presence of clinical signs observed at physical evaluation by the doctor or on the combination of both.…”
Section: Diagnosismentioning
confidence: 99%
“…Hendrickson et al (2009) also agree that lipoatrophy is one of the most common manifestations associated with the use of ARV and cite a frequency range of 13 to 63%. Viskovic et al (2009) believe that lipoatrophy is the most common and disfiguring of the body changes of the syndrome. They evaluated 151 patients with HIV, of whom about 39% reported lipoatrophy in some place, while about 45% of the physicians noticed fat loss in the clinical examination.…”
Section: Epidemiologymentioning
confidence: 99%